2018
DOI: 10.34256/ajir1814
|View full text |Cite
|
Sign up to set email alerts
|

Productive Vocabulary Knowledge of ESL Learners

Abstract: The paper seeks to investigate the level of productive knowledge of ESL learners, the writing quality and the relationship between the vocabulary knowledge and the writing quality. 150 final year students of English language in a university in Nigeria were randomly selected as respondents. The respondents were asked to write an essay of 300 words within one hour. The essays were typed into Vocab Profiler of Cobb (2002) and analyzed the Lexical Frequency Profile of the respondents. The essays were also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…(Misbah, Mohamad, Yunus, & Ya'acob, 2017) where their findings conclude that students' weakness in writing is due to lack of vocabulary (Usman & Abdullahi, 2018). Several recent studies on student lexicon also revealed that productive vocabulary is predictor of writing quality of second language learners of English (Usman & Abdullahi, 2018). These studies reported similar findings of earlier studies on the relationship between writing quality and students' lexicon (Astika 1993;eg.Engber 1995;Laufer & Nation 1995;Staehr 2008;Olinghouse & Wilson 2013).…”
Section: Introducationsupporting
confidence: 55%
See 4 more Smart Citations
“…(Misbah, Mohamad, Yunus, & Ya'acob, 2017) where their findings conclude that students' weakness in writing is due to lack of vocabulary (Usman & Abdullahi, 2018). Several recent studies on student lexicon also revealed that productive vocabulary is predictor of writing quality of second language learners of English (Usman & Abdullahi, 2018). These studies reported similar findings of earlier studies on the relationship between writing quality and students' lexicon (Astika 1993;eg.Engber 1995;Laufer & Nation 1995;Staehr 2008;Olinghouse & Wilson 2013).…”
Section: Introducationsupporting
confidence: 55%
“…However previous studies on the depth and breath of students' lexicon revealed that students' lexicon is limited, ( Mokhtar, Mohd Rawian, & Singh, 2016;Usman & Abdullahi ,2018) and did not reached the lexical threshold recommended in the previous research (Staehr, 2008;Douglas, 2013).…”
Section: Lexical Items In Academic Languagementioning
confidence: 68%
See 3 more Smart Citations